Potential and Quantum Threshold Voltage Modeling of Gate-All-Around Nanowire MOSFETs - M. Karthigai Pandian; N. B. Balamurugan; A. Pricilla (Active and Passive Electronic Components)
An improved physics-based compact model for a symmetrically biased gate-all-around (GAA) silicon nanowire transistor is proposed. Short channel effects and quantum mechanical effects caused by the ultrathin silicon devices are considered in modelling the threshold voltage. Device geometrics play a very important role in multigate devices, and hence their impact on the threshold voltage is also analyzed by varying the height and width of silicon channel. The inversion charge and electrical potential distribution along the channel are expressed in their closed forms. The proposed model shows excellent accuracy with TCAD simulations of the device in the weak inversion regime.